THE MIDDLE PLEISTOCENE DEPOSITS OF THE ROMAN BASIN (LATIUM, ITALY):AN INTEGRATED APPROACH OF MAMMAL BIOCHRONOLOGY AND SEQUENCE STRATIGRAPHY (Rivista italiana di Paleontologia e Stratigrafia, 2004)
The biochronological setting proposed for the Plio-Pleistocene large mammal faunas of the Italian peninsula is based on the definition of faunal units (FUs) and mammal ages (MAs). Many evidences suggest that a multidisciplinary approach could enable us to better understand the actual meaning of a given faunal assemblage taking into account sedimentological and physical stratigraphic studies of the sedimentary successions in which local mammal faunas occur. The Pleistocene deposits of the Roman Basin can be considered a significant model to test this integrated approach. The detailed study of this sedimentary succession, in terms of facies analysis and sequence stratigraphy, sets some physical and temporal constrains to the occurrence of faunal complexes because the allocyclic control (climate and eustatic variations) on both landscape and stratigraphical evolution can affect the association type of mammal faunas. A correlation scheme between the Roman Pleistocene sequence-stratigraphic units and the mammal biochrons has been proposed; this approach constitutes a first tentative to connect the mammal fauna remains to the sedimentary processes which are responsible of their transport, stock and potential preservation in the depositional environments and to collocate this fauna in the systems tracts of the fourth-order depositional sequences recognised in the local Roman Basin Pleistocene succession.